2022
DOI: 10.1111/ajt.17172
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis confers an increased mortality risk in orthotopic heart transplant recipients

Abstract: Novel risk stratification and non-invasive surveillance methods are needed in orthotopic heart transplant (OHT) to reduce morbidity and mortality post-transplant. Clonal hematopoiesis (CH) refers to the acquisition of specific gene mutations in hematopoietic stem cells linked to enhanced inflammation and worse cardiovascular outcomes.The purpose of this study was to investigate the association between CH and OHT.Blood samples were collected from 127 OHT recipients. Error-corrected sequencing was used to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…Within a prospective subgroup, pretransplant specimens could detect 83% of DDR variants that occurred after transplant, including all variants with VAF greater than 1%. This finding is unique to lung transplant recipients; recently, the reported incidence of CH in DDR genes ( TP53 and PPM1D ) was only 4% in heart transplant recipients ( 30 ). DDR genes TP53 , ATM , and PPM1D are known to have regulatory roles in cell division, survival, and tumor suppression ( 2 ).…”
Section: Discussionmentioning
confidence: 84%
“…Within a prospective subgroup, pretransplant specimens could detect 83% of DDR variants that occurred after transplant, including all variants with VAF greater than 1%. This finding is unique to lung transplant recipients; recently, the reported incidence of CH in DDR genes ( TP53 and PPM1D ) was only 4% in heart transplant recipients ( 30 ). DDR genes TP53 , ATM , and PPM1D are known to have regulatory roles in cell division, survival, and tumor suppression ( 2 ).…”
Section: Discussionmentioning
confidence: 84%
“…However, specific CH mutations may have distinct inflammatory profiles. 9,22 We observed that DNMT3A-driven CH was associated with IL-9 and CXCL12. TET2-driven CH was associated with the higher circulating levels of a different array of cytokines/chemokines including troponin I.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, somatic mutations in haematopoietic stem cells occurring in the first decades of life are polyclonal and have unknown long-term effects. 27,28 Many studies have focused on the most common gene variants, such as DNMT3A, TET2 and ASXL1 9,12,22,26,29 , present in 17% of HCM patients with CH mutations. Unsurprisingly, we found that HCM patients with these specific genes showed worse clinical phenotype and outcome, similarly to other patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As will be reviewed here, the evidence implicating CH in poor cardiovascular outcomes is extensive, which is likely a primary driver for the association of CH with decreased OS in the general population [16]. The relationship between CH and coronary artery disease (CAD) was the first non-oncologic outcome to be recognized [15], with further cardiologic studies also linking CH to progression of heart failure [17][18][19][20], aortic aneurysm [21], pulmonary hypertension [22], deterioration from cardiogenic shock [23], aortic stenosis [24], poor outcomes after TAVR [25] or orthotopic heart transplantation [26], and increased sensitivity to cardiotoxic chemotherapy [27]. Here we will review the evidence connecting CH to cardiovascular outcomes, mechanistic explanations, potential practice changes, and future research directions.…”
Section: Introductionmentioning
confidence: 99%